Assessing walking steps and its relationship with nutritional status among adults in Kuala Terengganu - Leong, Rhu Chyi; Asma’ Ali; Noor Salihah Zakaria; Hayati Mohd Yusof (Penerbit Universiti Kebangsaan Malaysia, 2017)
To date, 10,000 steps per day are extensively promoted as a target for achieving health-related benefits. Despite mounting evidence on the numerous health benefits provided by sufficient physical activities, little is known about physical activity levels in terms of walking steps of adults in Kuala Terengganu and the relationship between activity levels and nutritional status. Therefore, this study was aimed to assess daily walking steps taken as well as the relationship with nutritional status among 100 adults in Kuala Terengganu, Malaysia. Walking activity was assessed using an Omron HJ-005 pedometer, while nutritional status was assessed through BMI, waist circumference, blood pressure, fasting glucose and serum lipid concentration. On average, participants recorded 5796 (4186) steps per day, below the recommended target of 10,000 walking steps goal. There was no significant relationship found between number of walking steps and nutritional status. Remarkably, daily walking steps were found to be significantly correlated with the International Physical Activity Questionnaire (IPAQ), where r = 0.26, p < 0.01, indicating that pedometers are good indicators of physical activity levels. Nonetheless, an awareness program to increase the level of leisure-type physical activities such as walking is much encouraged in this population.